Catalase C262T genetic variation and cancer susceptibility: A comprehensive meta-analysis with meta-regression and trial sequential analysis. Issue 3 (September 2022) - Barek, Md Abdul; Jafrin, Sarah; Aziz, Md. Abdul; Islam, Mohammad Safiqul
Several genetic association studies have analyzed the link between the catalase ( CAT ) C262T variant and different cancers, but the findings remain controversial. Our research centered on establishing a comprehensive correlation between the C262T variant and different cancers. This study was conducted using RevMan 5.4 software following the PRISMA 2020 guidelines. For this meta-analysis, 53 case-control studies (18, 258 cases and 47, 476 controls) were chosen. The analysis revealed that three genetic models were statistically linked ( P  < 0.05) to overall cancer susceptibility in codominant model 2 (COD2): odds ratio (OR) = 1.16, COD3: OR = 1.21, recessive model (RM): OR = 1.20). After stratification by ethnicity, a significant link ( P  < 0.05) was found in Caucasians (COD2: OR = 1.18, COD3: OR = 1.17, over-dominant model (ODM): OR = 1.19) and Asians (COD3: OR = 1.49). Subgroup analyses revealed a significant correlation ( P  < 0.05) with blood-and-bone-marrow-related cancer, skin cancer, gastrointestinal-tract-related cancer, prostate cancer, and gynecologic cancer. Three genetic models in population-based controls (COD2: OR = 1.19, COD3: OR = 1.17, RM: OR = 1.19) and two genetic models in hospital-based controls (COD3: OR = 1.40, RM: OR = 1.24) were found to be significantly correlated ( P  < 0.05) with cancer. Also, three genetic models for polymerase chain reaction-restriction fragment length polymorphism (COD3: OR = 1.46; RM: OR = 1.34, ODM: OR = 0.80) and three models for MALDI-TOF + MassARRAY (COD2: OR = 1.32, RM: OR = 1.26, allele model: OR = 1.14) genotyping methods showed significant association ( P  < 0.05) with cancer. The meta-regression showed that the quality scores might be a source of significant heterogeneity under the COD2 model (coefficient = 0.176, P  = 0.029). Trial sequential analysis also validated the adequacy of the sample size on overall findings. Our results indicate that CAT C262T variant is associated with overall cancer susceptibility, especially in Caucasians and Asians. This variant may also be associated with blood-and-bone-marrow-related, GIT-related, prostate, skin, and gynecological cancers.